New models for age estimation and assessment of their accuracy using developing mandibular third molar teeth in a Thai population - P. Duangto (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Age estimation using developing third molar teeth is considered an important and accurate technique for both clinical and forensic practices. The aims of this study were to establish population-specific reference data, to develop age prediction models using mandibular third molar development, to test the accuracy of the resulting models, and to find the probability of persons being at the age thresholds of legal relevance in a Thai population. A total of 1867 digital panoramic radiographs of Thai individuals aged between 8 and 23 years was selected to assess dental age. The mandibular third molar development was divided into nine stages. The stages were evaluated and each stage was transformed into a development score. Quadratic regression was employed to develop age prediction models. Our results show that males reached mandibular third molar root formation stages earlier than females. The models revealed a high correlation coefficient for both left and right mandibular third molar teeth in both sexes (R = 0.945 and 0.944 in males, R = 0.922 and 0.923 in females, respectively). Furthermore, the accuracy of the resulting models was tested in randomly selected 374 cases and showed low error values between the predicted dental age and the chronological age for both left and right mandibular third molar teeth in both sexes (−0.13 and −0.17 years in males, 0.01 and 0.03 years in females, respectively). In Thai samples, when the mandibular third molar teeth reached stage H, the probability of the person being over 18  years was 100 % in both sexes.